Isolated low-grade solid organ injuries in children following blunt abdominal trauma: Is it time to consider discharge from the emergency department?. Issue 5 (November 2020) - Plumblee, Leah; Williams, Regan; Vane, Dennis; Zhang, Jingwen; Jensen, Aaron; Naik-Mathuria, Bindi; Evans, Lauren; Streck, Christian J.
Abstract : INTRODUCTION: Acute intervention (AI) for solid organ injury (SOI) is rare in hemodynamically stable children. Pediatric guidelines recommend admission with follow-up laboratories, even for low-grade injuries. METHODS: Data sets from two large multicenter prospective observational studies were used to analyze a cohort of children (age, <17 years) with grade I to III SOI following blunt abdominal trauma. Children with hollow viscus injuries were excluded. Patients were divided into ( a ) those with or without other major injuries (OMIs) (traumatic brain injury, hemothorax or pneumothorax, pelvic fracture, urgent orthopedic or neurosurgical operations) and (b) with grade I or II versus grade III injuries. Outcomes included AIs (transfusion, angiography, abdominal operation) and disposition (admission unit and length of stay). RESULTS: There were 14, 232 children enrolled in the two studies, and 791 patients had a SOI (5.6%). After excluding patients with hollow viscus injuries and higher-grade SOIs, 517 patients with a grade I to III SOI were included, and 262 of these had no OMI. Among patients with no OMI, none of 148 patients with grade I or II SOI underwent AI, while only 3 of 114 patients with grade III injuries underwent AI (3 transfusions/1 angioembolization). All three had hemoperitoneum; two of three had an additional organ with a grade II injury. Among grade I and II SOIs with no OMI, 28 (18.9%) of 148 were admitted to an intensive care unit, 110 (74.3%) of 148 to floor, and 7 (4.7%) of 148 discharged home from emergency department; median length of stay 2 days. Among grade III SOIs with no OMI, 38 (33.3%) of 114 were admitted to an intensive care unit and 61.4% to the floor; median length of stay was 4 days. Among 255 patients with a grade I to III SOI and other major organ system injuries, 31 (12.2%) underwent AI. CONCLUSION: No patient with a grade I and II SOI and no OMI following blunt abdominal trauma received intervention, suggesting that patients with low-grade SOI without OMIs could be safely observed and discharged from the emergency department. LEVEL OF EVIDENCE: Therapeutic study, level IV.